Exploring Digital Literacy Skills of Prospective Indonesian EFL Teachers - Christiani, Natalia; Tungka, Novalita Fransisca; Nainggolan, Romauli (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Understanding EFL students’ levels of digital literacy is a vital step to improve the quality of English teaching and learning. This paper explored the levels of digital literacy skills of prospective Indonesian EFL teachers in the matter of their readiness for the integration and implementation of digital tools in their language learning practices. The respondents were three hundred thirty-six students majoring in the English Language Education department across cultural regions in Indonesia. A questionnaire was distributed online to gather data. The data were then tabulated and interpreted descriptively. The analysis results reported that the prospective Indonesian EFL teachers’ level of digital literacy was moderate. The discussion in this paper focuses on their digital literacy skills in terms of creative, technological, personal security, internet safety, problem-solving, information, communication or netiquette, and navigation. The findings of this study will provide a useful reference to improve learning practices and the integration and implementation of digital tools in English teaching and learning contexts.